The annihilator method for computing particular solutions to partial differential equations - Golberg, M.A.; Chen, C.S.; Rashed, Y.F. (Engineering analysis with boundary elements, 1999)
We generalize the well-known annihilator method, used to find particular solutions for ordinary differential equations, to partial differential equations. This method is then used to find particular solutions of Helmholtz-type equations when the right hand side is a linear combination of thin plate and higher order splines. These particular solutions are useful in numerical algorithms for solving boundary value problems for a variety of elliptic and parabolic partial differential equations.